2022
DOI: 10.1002/adma.202207544
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Stretchable, Highly Efficient Organic Solar Cells Enabled by Polymer Donors Featuring Hydrogen‐Bonding Spacers

Abstract: Intrinsically stretchable organic solar cells (IS‐OSCs), consisting of all stretchable layers, are attracting significant attention as a future power source for wearable electronics. However, most of the efficient active layers for OSCs are mechanically brittle due to their rigid molecular structures designed for high electrical and optical properties. Here, a series of new polymer donors (PDs, PhAmX) featuring phenyl amide (N1,N3‐bis((5‐bromothiophen‐2‐yl)methyl)isophthalamide, PhAm)‐based flexible spacer (FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 81 publications
(19 reference statements)
0
38
0
Order By: Relevance
“…The performance of organic photovoltaics (OPVs) can be easily tuned by tailoring the chemical structures of organic components in the photoactive layer. Since the first report of A-DA′D-A-type non-fullerene acceptors (NFAs), the power conversion efficiencies (PCEs) of OPVs have been rapidly improved to greater than 19%. This significant progress is mainly due to the delicate modifications of NFA structures. In general, there are two strategies in modifying NFAs, tailoring of the aromatic heterocycles in the conjugated backbone and tuning the aliphatic/aromatic side-groups. The main efforts have been devoted to enhancing the molecular planarity for improving the light absorption and electron mobility of NFAs. The additional halogenation on either π-core or terminal groups can further modulate the frontier molecular orbitals and the molecular packing/aggregation properties of NFAs. …”
Section: Introductionmentioning
confidence: 99%
“…The performance of organic photovoltaics (OPVs) can be easily tuned by tailoring the chemical structures of organic components in the photoactive layer. Since the first report of A-DA′D-A-type non-fullerene acceptors (NFAs), the power conversion efficiencies (PCEs) of OPVs have been rapidly improved to greater than 19%. This significant progress is mainly due to the delicate modifications of NFA structures. In general, there are two strategies in modifying NFAs, tailoring of the aromatic heterocycles in the conjugated backbone and tuning the aliphatic/aromatic side-groups. The main efforts have been devoted to enhancing the molecular planarity for improving the light absorption and electron mobility of NFAs. The additional halogenation on either π-core or terminal groups can further modulate the frontier molecular orbitals and the molecular packing/aggregation properties of NFAs. …”
Section: Introductionmentioning
confidence: 99%
“…A high power conversion efficiency (PCE) has been demonstrated for small-area devices, recently demonstrating a high chance of being commercialized in the future. The improvement in PCE mainly relies on the innovation of active layer materials and the improvement of interfacial layers. Newly developed nonfullerene acceptors with strong absorption in the visible range have boosted device performance for small areas below 1 cm 2 . The morphological stability in blend films was also improved by introducing the nonfullerene material system . The introduction of interfacial layers was also demonstrated to be beneficial for device stability and performance. By selecting appropriate interfacial layers, the energy level alignment at the electrode/active layer interfaces and the built-in electric field can be tailored to enhance the collection efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, new molecular designs of donors and acceptors have successfully improved the stretchability and PCEs in OPVs. A recent report showed that a donor molecule with flexible spacers could achieve great stretchability in an OPV with a PCE of 12.73%, a record efficiency in stretchable OPVs . The PCE retention is over 80% under ∼30% strain.…”
Section: Introducing Stretchability Through Heterostructure Engineeringmentioning
confidence: 99%